2008
DOI: 10.1038/sj.bjc.6604617
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of MUC1 alternative splicing in human tissues

Abstract: The membrane mucin MUC1 is aberrantly expressed in a variety of cancers, and in stomach, it is a ligand for Helicobacter pylori where it plays a role in gastric carcinogenesis. Splicing variation, leading to a 9-amino acid insertion in the signal peptide region, was proposed to be because of a single-nucleotide polymorphism (rs4072037) at the 5 0 end of exon 2, but is also reported to be cancer-associated. However, the effect of rs4072037 on this splicing event in healthy non-cancer tissues and on the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 33 publications
1
60
0
Order By: Relevance
“…(53,54) The A allele of rs4072037 identified using the GWAS is in a linkage disequilibrium with the S allele in Japanese and Caucasian patients. (13,55) The results of these association studies on different ethnic populations strongly support the result of the Japanese GWAS; MUC1 is a GC susceptibility gene.…”
Section: à7supporting
confidence: 66%
See 1 more Smart Citation
“…(53,54) The A allele of rs4072037 identified using the GWAS is in a linkage disequilibrium with the S allele in Japanese and Caucasian patients. (13,55) The results of these association studies on different ethnic populations strongly support the result of the Japanese GWAS; MUC1 is a GC susceptibility gene.…”
Section: à7supporting
confidence: 66%
“…3). (13,55) Consequently, the nine amino acid deletion in the second exon changes the supposed cleavage site of the N-terminal signal peptide, which might lead to a difference in the function of the encoded protein between the two splicing variants. It is understood that, in GC and other cancer cells that have lost cell polarity, the MUC1 protein interacts freely with other molecules including membrane receptors involved in cell growth and, consequently, it acts as an oncoprotein; in contrast, in normal epithelial cells, MUC1 is restricted to the apical surface of the cells where the interaction with other molecules is limited and it acts as a barrier against exogenous insults to the cells.…”
Section: à7mentioning
confidence: 99%
“…Two previous studies also found genetic variations in MUC1 that were associated with GC susceptibility (Jia et al, 2010;Xu et al, 2009). Regarding rs4072037, the MUC1 A/G polymorphism in exon 2 was reported to control alternative splicing of the 5'-exon 2 region in both fulllength transcripts and those lacking the polymorphic tandem repeat domain (Ng et al, 2008). Subsequently, the polymorphism was observed to disrupt the physiological functions of MUC1, which is important for protection of the gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The final selection comprised 4 SNPs. Additionally, SNP rs4072037 determining the major splicing variants of MUC1 and regulating MUC1 expression in the gastric epithelium (Ng et al, 2008;Xu et al, 2009) was also selected for this study.…”
Section: Selection Of Snpsmentioning
confidence: 99%
“…Some works have documented the role of MUC1 in the H. pylori infection and gastric cancer risk. Thus, MUC1 is often aberrantly expressed in stomach cancer, and it is a ligand for H. pylori (Ng et al, 2008). Susceptibility to H. pylori infection and gastric cancer appears to be associated with MUC1 allele length (Costa et al, 2008;Vinall et al, 2002 (Xu et al, 2009;Jia et al, 2010;Zhang et al, 2011) with controversial results (Abnet et al, 2010;He et al, 2013).…”
Section: Introductionmentioning
confidence: 99%